1994
DOI: 10.1002/bit.260440505
|View full text |Cite
|
Sign up to set email alerts
|

Biological sulphate reduction using gas‐lift reactors fed with hydrogen and carbon dioxide as energy and carbon source

Abstract: Feasibility and engineering aspects of biological sulphate reduction in gas-lift reactors were studied. Hydrogen and carbon dioxide were used as energy and carbon source. Attention was paid to biofilm formation, sulphide toxicity, sulphate conversion rate optimization, and gas-liquid mass transfer limitations. Sulphate-reducing bacteria formed stable biofilms on pumice particles. Biofilm formation was not observed when basalt particles were used. However, use of basalt particles led to the formation of granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
3
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 171 publications
(93 citation statements)
references
References 19 publications
3
77
3
1
Order By: Relevance
“…The mat thickness increase with time may be linked to the displacement of the oxygensulfide interface from the wood surface toward the seawater as observed on other Epsilonproteobacteria mats (Wirsen et al, 2002;Sievert et al, 2007). This displacement limits the penetration of potential electron acceptors like oxygen and nitrate, thus promoting the development of anaerobic and nitrate depleted niches (Van Houten et al, 1994;Okabe et al, 2005) on the wood side of the mat as shown by the microsensor measurements taken in our second experiment (Figure 5c). These new ecological niches presented ideal conditions for the development of sulfate-reducing bacteria but were probably not favorable for chemoorganotrophic bacteria, like A. nitrofigilis (Otu8), which disappeared as the mat grew.…”
Section: Ecological Succession During Epixylic Mat Formationsupporting
confidence: 53%
“…The mat thickness increase with time may be linked to the displacement of the oxygensulfide interface from the wood surface toward the seawater as observed on other Epsilonproteobacteria mats (Wirsen et al, 2002;Sievert et al, 2007). This displacement limits the penetration of potential electron acceptors like oxygen and nitrate, thus promoting the development of anaerobic and nitrate depleted niches (Van Houten et al, 1994;Okabe et al, 2005) on the wood side of the mat as shown by the microsensor measurements taken in our second experiment (Figure 5c). These new ecological niches presented ideal conditions for the development of sulfate-reducing bacteria but were probably not favorable for chemoorganotrophic bacteria, like A. nitrofigilis (Otu8), which disappeared as the mat grew.…”
Section: Ecological Succession During Epixylic Mat Formationsupporting
confidence: 53%
“…A good agreement between predicted and actual COD removal is found for the first experiment (COD was not used in the calibration), and between the actual and predicted sulphate and COD removal in the second experiment. 2 van Houten et al (1994) operated a sulphate reducing gas lift reactor, fed carbon dioxide and hydrogen. Pumice particles were used as the carrier material giving the reactor an active volume of 4.5 litres.…”
Section: Test Simulation No4-packed Bed Fed Sewage Sludgementioning
confidence: 99%
“…Such electron donors include hydrogen, synthesis gas, methanol, ethanol, acetate, lactate, propionate, butyrate, sugar, and molasses (Liamleam and Annachhatre 2007), many of which have been extensively investigated as electron donor for SR in bioreactors (Table 2). According to van Houten (1996) hydrogen is the best electron donor at large scale ([5-10 kmol SO 4 2-h -1 ), while ethanol is an interesting electron donor at smaller and middle scale.…”
Section: Electron Donors For Sulfate Reductionmentioning
confidence: 99%
“…A GLB is usually equipped with a threephase separator (Esposito et al 2003;van Houten et al 1994;Weijma et al 2002) or an external settler (Sipma et al 2007) to retain the biomass in the system. GLBs can be operated with (van Houten et al 1994) or without (Sipma et al 2007) carrier material like pumice and basalt. Metal-sulfides produced in gas-lift bioreactors can also act as carrier material for the microorganisms.…”
Section: Reactor Typementioning
confidence: 99%